LEARNING EXPERIENCES AND ENGLISH EXPOSURE OF ENGLISH EDUCATION STUDENTS AT UNIVERSITAS PALANGKA RAYA - Matondang, Leni Romarta; Inggrita Vadeltine Panyat, Maria; Subhan Fikri, Muhammad; Fauzan, Akhmad (Universitas Jambi, 2025)
This study aims to describe the learning experience and English exposure level of English Language Education students at Palangka Raya University. The study used mixed methods with data collection through closed-ended questionnaires and open-ended questions, which were analyzed descriptively quantitatively and qualitatively. The results show that most students have a fairly positive learning experience, especially in terms of motivation and engagement. However, the active use of English is still inconsistent. Informal exposure to English through digital media appears to be more dominant, with a higher tendency of utilizing entertainment content than educational content. Meanwhile, the use of English in formal contexts and social environments is still relatively limited. These findings emphasize the importance of learning strategies that are able to combine formal, informal, and self-learning approaches in a balanced manner to support students' overall mastery of English.